Analisis Perilaku Konsumen Perspektif Ekonomi Islam Dalam Transaksi Jual Beli (Di Pasar Rakyat Pekkabata Kab Pinrang) - A Rahmat Hidayat; Mustamin B; Andi Bisyriani (Mappideceng:Jurnal Ekonomi Syariah, 2025)
This study aims to analyze the phenomenon of consumer behavior at Pekkabata Traditional Market by considering the principles of Islamic economics that influence their purchasing decisions. With this, it is expected to identify key factors that shape consumer shopping behavior in a context that is in accordance with sharia. This study uses qualitative descriptive research, namely a research approach that describes data in depth. Data collection techniques include observation, interviews, and documentation, which are analyzed using qualitative descriptive methods. The results of this study indicate that: 1) Consumer behavior in the Pekkabata market in conducting transactions has been carried out in accordance with Islamic law, where consumers carry out a fair, honest and non-harmful bargaining process for other parties. 2) Consumer behavior factors in the Pekkabata market are more influenced by cultural and personal factors, because consumer behavior tends to be sensitive to price due to limited income and consumers prefer affordable products according to their needs.